Stability and Thermal Conductivity Characteristic of Carbon Nanotube Based Nanofluids - N. M., Fadhillahanafi; K. Y., Leong; M. S., Risby (Universiti Malaysia Pahang, 2013)
Heat transfer fluids such as water, ethylene glycol and engine oil are commonly used in heat exchanger applications. However these fluids posses low thermal conductivity. The technology advancement in nanotechnology has enabled the nano size particles to be included in a base fluid. This new generation of fluid is known as nanofluids. Producing a stable nanofluid with improved thermal conductivity is a challenging process. The suspended nanoparticles tend to sediment with respect to time. In the present study, multiwall carbon nanotubes (MWCNT) based nanofluids with or without surfactant were investigated in the aspect of stability and thermal conductivity. Study implies that nanofluids added with polyvinylpyrrolidone (PVP) surfactant exhibit better stability compared to nanofluids without surfactant. About 22.2% thermal conductivity improvement was observed for water containing 0.5wt% of MWCNT and 0.1wt% of PVP surfactant. The thermal conductivity also increases with the increasing of MWCNT’s weight fraction.